Mengemas Kelas Bahasa Inggris (EFL) melalui Joyful Learning Based Social Constructivism Pedagogy - Huda, Husnul; Dewi, Nuna Mustikawati; Widyaningrum, Lulut (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2017)
Joyful Learning as a learning process in which there is a strong cohesion between educators and learners, without any feelings of forced or depressed to make learners dare to do, dare to try, dare to ask, express opinions, and defend opinions so as not to fear wrong, ridiculed , underestimated and depressed. The purpose of this article is to illustrate the empowerment of madrasah English teachers with Joyful Learnig-Based Social Constructivism Pedagogy in the EFL Class. In implementing the concept of joyful based social constructivism pedagogy, the program is designed in four stages including socialization and training; class-class modeling; teacher engagement in classroom practice; and mentoring teachers to practice independently in the classes. In general, the English teachers in the two accompanying madrassas have been able to implement the concept of joyful based social constructivism pedagogy through a variety of methods and techniques that vary especially in brainstorming and ice breaking.Joyful Learning  sebagai suatu proses pembelajaran yang didalamnya terdapat sebuah kohesi yang kuat antara pendidik dan peserta didik, tanpa ada perasaan terpaksa atau tertekan sehingga membuat peserta didik berani berbuat, berani mencoba, berani bertanya, mengemukakan pendapat, dan mempertahankan pendapat  sehingga tidak takut salah, ditertawakan, diremehkan  dan  tertekan. Tujuan dari artikel ini adalah menggambarkan pemberdayaan guru bahasa Inggris madrasah dengan Joyful Learnig-Based Social Constructivism Pedagogy dalam Kelas EFL. Dalam mengimplemetasikan konsep joyful based social constructivism pedagogy ini, program didesain dalam empat tahap yang meliputi sosialisasi dan pelatihan; pemberian modelling dikelas-kelas; pelibatan guru dalam praktik di kelas-kelas; dan pendampingan guru untuk praktik secara mandiri di kelas-kelas. Secara umum, para guru bahasa Inggris di dua madrasah yang didampingi sudah mampu mengimplemetasikan konsep joyful based social constructivism pedagogy melalui berbagai macam metode dan teknik yang bervariasi khususnya dalam brainstorming dan ice breaking.